Definition and grading of anastomotic leakage following anterior resection of the rectum: a proposal by the International Study Group of Rectal Cancer - Rahbari, Nuh Nabi; Weitz, Jürgen; Hohenberger, Werner; Heald, Richard J.; Moran, Brendan; Ulrich, Alexis; Holm, Torbjörn; Wong, W. Douglas; Tiret, Emmanuel; Moriya, Yoshihiro; Laurberg, Søren; den Dulk, Marcel; et al. (Surgery, 2010)
Background - Anastomotic leakage represents a major complication after anterior resection of the rectum. The incidence of anastomotic leakage varies considerably among clinical studies in part owing to the lack of a standardized definition of this complication. The aim of the present article was to propose a definition and severity grading of anastomotic leakage after anterior rectal resection. - Methods - After a literature review a consensus definition and severity grading of anastomotic leakage was developed within the International Study Group of Rectal Cancer. - Results - Anastomotic leakage should be defined as a defect of the intestinal wall at the anastomotic site (including suture and staple lines of neorectal reservoirs) leading to a communication between the intra- and extraluminal compartments. Severity of anastomotic leakage should be graded according to the impact on clinical management. Grade A anastomotic leakage results in no change in patients’ management, whereas grade B leakage requires active therapeutic intervention but is manageable without re-laparotomy. Grade C anastomotic leakage requires re-laparotomy. - Conclusion - The proposed definition and clinical grading is applicable easily in the setting of clinical studies. It should be applied in future reports to facilitate valid comparison of the results of different studies.
Online verfügbar 11. Dezember 2009
Gesehen am 10.05.2023